The Effect of Accessibility and Destination Image on Revisit Intention to Pelaruga Waterfall In Langkat Regency - Syeh Nedi Bremana Pandia; Alfifto; Wan Suryani; Eka Dewi; Syafrida Hafni (SAJMR : Southeast Asian Journal of Management and Research, 2026)
The development of Pelaruga Waterfall tourism has been quite rapid in Langkat Regency. However, the interest in revisiting the site has not met expectations, presumably due to difficult road access and the poor image of the destination. The Purpose of study was to determine the effectc of accessibility and Destination Image on revisit intention to Pelaruga Waterfall In Langkat Regency. The type of quantitative descriptive research. The Population is 268.769 tourists who have visited the Pelagura Waterfall tourist attraction in Langkat Regency throughout 2024. The sample in this study used purposive sampling consisting of 100 respondents who had visited the Pelaruga Waterfall in Langkat Regency. The analysis techniques uses statitical model consisting of validity, reliability, classical assumptions, multiple linear regression, t-test, F-test and coeffcient of determination (R2) using SPSS (Statistical Produk and Service Solutions ) sofware version 23. Data collection methods were through interviews, questionnaires and documentation studies. The tests carried out show that accessibility and destination image partially have a positive and significant effect on revisit intention. The Adjusted R Square value obtained from the results of testing the Determinant Coefficient (R2) on revisit intention is 0.741, meaning that 74,1% can be explained by accessibility and destination image. Meanwhile, the remaining 25,9% can be explained by other factors not examined in this study.